Prasophyllum and its associated mycorrhizal fungi - McQualter, Emily; Cross, Rob; B. McLean, Cassandra; Y. Ladiges, Pauline (Lankesteriana: International Journal on Orchidology, 2007)
In Victoria, there are over 330 taxa of orchid and at least half of those are threatened. The potential extinction of many of these orchids is largely due to habitat destruction caused by degradation from agriculture, industrial development and urbanisation. Effective conservation ultimately depends on the reintroduction to field sites to reinforce depleted populations. For terrestrial orchids, seed germination is the preferred method of propagation as it allows genetic variability to be maintained (Batty et al. 2006).